Using Inquiry-Based Learning to Enhance Immunology Laboratory Skills - Demaria, Maria; Barry, Anita; Murphy, Kim (Frontiers in Immunology, 2019)
A challenge in teaching immunology in the undergraduate laboratory is to encompass the many varied skills that need to be applied when performing an investigative study of such a complex area. It requires background knowledge, data analysis skills, critical thinking, and design capacities to include relevant controls and applications of particular techniques to answer a research question. It also requires strong technical skills. One such approach is to use inquiry-based learning which allows students a more proactive and integrative role in their learning. In one of our final year immunology units we have incorporated an inquiry-based exercise that runs across four five-hour sessions. Students are given two cornerstone immunology techniques (ELISA and a flow cytometry-based cytokine bead array), which they use to formulate a study investigating inflammation. Stage one is to design the experiment with some guidance from teaching staff, stage two is to perform the experiment, and then finally students are required to analyze the data, apply appropriate statistics, and write a report outlining their findings. This approach provides students ownership of the process and allows them the opportunity to investigate a real-world problem rather than just attempting to obtain the expected “correct answer”. Feedback from both students and staff has been positive with strong engagement and high quality reports produced.